2021
DOI: 10.1111/tme.12780
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic tranexamic acid use in non‐cardiac surgeries at high risk for transfusion

Abstract: Background Tranexamic acid (TXA) reduces transfusion in a wide range of surgical populations, although its real‐world use in non‐cardiac surgeries has not been well described. The objective of this study was to describe prophylactic TXA use in non‐cardiac surgeries at high risk for transfusion. Methods This is a retrospective cohort study of all adult patients undergoing major non‐cardiac surgery at ≥5% risk of perioperative transfusion at five Canadian hospitals between January 2014 and December 2016. Canadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The PBM strategy has since been incorporated in other parts of the world, including the USA, Austria, Australia and Netherlands 42 . Tranexamic acid has also been shown to consistently reduce RBCs transfusion in a wide range of surgical populations 43 . Despite of these advances, Hb at a level between 7 and 10 g/dl represent an area for further refinement in perioperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PBM strategy has since been incorporated in other parts of the world, including the USA, Austria, Australia and Netherlands 42 . Tranexamic acid has also been shown to consistently reduce RBCs transfusion in a wide range of surgical populations 43 . Despite of these advances, Hb at a level between 7 and 10 g/dl represent an area for further refinement in perioperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…42 Tranexamic acid has also been shown to consistently reduce RBCs transfusion in a wide range of surgical populations. 43 Despite of these advances, Hb at a level between 7 and 10 g/dl represent an area for further refinement in perioperative blood transfusion. The POTTS system included four variables that are readily available during routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…13 The results of small randomized-controlled trials, as well as subsequent systematic reviews and meta-analyses, demonstrate that perioperative TXA is effective at reducing surgical blood loss and allogeneic transfusion in orthopedic surgery. [97][98][99][100] A recent retrospective analysis assessed prophylactic TXA use in noncardiac surgeries at high risk for blood transfusion in 14,300 patients between 2014 and 2016. 98 The results demonstrated that TXA was most frequently used in patients undergoing orthopedic surgery (~41%) with a higher utilization for pelvic surgery (~68%) and hip arthroplasty (~67%).…”
Section: Txa In Orthopedic Surgerymentioning
confidence: 99%
“…[97][98][99][100] A recent retrospective analysis assessed prophylactic TXA use in noncardiac surgeries at high risk for blood transfusion in 14,300 patients between 2014 and 2016. 98 The results demonstrated that TXA was most frequently used in patients undergoing orthopedic surgery (~41%) with a higher utilization for pelvic surgery (~68%) and hip arthroplasty (~67%). This degree of TXA utilization was much higher than was observed for other types of noncardiac surgery.…”
Section: Txa In Orthopedic Surgerymentioning
confidence: 99%
See 1 more Smart Citation